The pandemic experiences of Ontario perinatal providers: a qualitative study - Sigourney Shaw-Churchill; Karen P. Phillips (BMC, 2023)
Abstract Background The COVID-19 pandemic has produced widespread disruptions for healthcare systems across Canada. Perinatal care in Ontario, Canada was subject to province-wide public health restrictions, reallocation of hospital beds and human health resources. To better understand the impacts of the pandemic on Ontario perinatal care, this study explored the perspectives of perinatal care providers about their clinical COVID-19 pandemic experiences. Methods Semi-structured key informant virtual interviews were conducted between August 2021 and January 2022 with 15 Ontario-based perinatal care providers. Recorded interviews were transcribed, and thematic content analysis used to identify major themes and subthemes. Results Participants were mainly women, practicing in Eastern and Central Ontario as health providers (obstetricians, nurses, midwives), allied regulated health professionals (social worker, massage therapist), and perinatal support workers (doula, lactation consultant). Major themes and subthemes were identified inductively as follows: (1) Impacts of COVID-19 on providers (psychosocial stress, healthcare system barriers, healthcare system opportunities); (2) Perceived impacts of COVID-19 on pregnant people (psychosocial stress, amplification of existing healthcare barriers, influences on reproductive decision making; minor theme- social and emotional support roles); (3) Vaccine discourse (provider empathy, vaccines and patient family dynamics, minor themes- patient vaccine hesitancy, COVID-19 misinformation); and (4) Virtual pregnancy care (benefits, disadvantages, adaptation of standard care practices). Conclusions Perinatal care providers reported significant stress and uncertainty caused by the COVID-19 pandemic and evolving hospital protocols. Providers perceived that their patients were distressed by both the pandemic and related reductions in pregnancy healthcare services including hospital limits to support companion(s). Although virtual pregnancy care impaired patient-provider rapport, most providers believed that the workflow efficiencies and patient convenience of virtual care is beneficial to perinatal healthcare.